A comprehensive evaluation framework for China's oil import sustainability with a projection pursuit and matter-element extension model. Issue 7 (3rd July 2021) - Deng, Shen; Mou, Siyu; Liu, Huifang
ABSTRACT: Given the serious imbalance between supply and demand for domestic oil resources, it is essential to accurately identify and measure the potential problems associated with oil imports to mitigate the negative influence of oil import uncertainty on China's energy security. This paper designs a comprehensive assessment index framework based on the dimensions of the supply chain and establishes an integrated model to evaluate the sustainability of China's oil imports from 2000 to 2017. The results show that since 2000, China's oil import sustainability has experienced apparent dynamic changes from a critical state to strong unsustainability and then weak unsustainability. External dependence remains the most significant threat, and high dependence on oil imports is the root cause. External supply sustainability may become the main long-term risk source in the future. Recommendations for improvements in oil import sustainability are proposed considering the less optimistic future trend.